Divorce Cases in Members of Indonesian Police Force: A Positive Law Perspective - Nur Mohamad Kasim; Trubus Semiaji (IAIN Manado, 2022)
This research aims to analyse the factors of divorce in members of a police force, the impacts, and alternatives offered by the court judge to overcome divorce problems from a positive law perspective, the juridical-sociological method. The study took place in the coverage area of Court in Gorontalo, Suwawa, and Limboto. Further, the present work applied a case approach and statute approach. The data from primary and secondary sources were collected from the literature study and field research. The results showed that the factors of divorce comprise: prolonged quarrelling, cheating, economic problems, and domestic violence. The divorce cases lead to several problems that impact the married couple, their children, and their shared wealth. Referring to the Islamic Law perspective, the court Judge provides several alternatives to optimise mediation as dispute settlement before divorce as a last resort. Moreover, the Judge provides post-divorce alternatives to ensure that the ex-husband gives the iddah and mut'ah allowances to his ex-wife and that the ex-husband still supports the children's development.